Impact of palbociclib plus letrozole on patient-reported health-related quality of life: results from the PALOMA-2 trial. (19th January 2018) - Rugo, H S; Diéras, V; Gelmon, K A; Finn, R S; Slamon, D J; Martin, M; Neven, P; Shparyk, Y; Mori, A; Lu, D R; Bhattacharyya, H; Bartlett, C Huang; et al.
Abstract: Background: Patient-reported outcomes are integral in benefit–risk assessments of new treatment regimens. The PALOMA-2 study provides the largest body of evidence for patient-reported health-related quality of life (QOL) for patients with metastatic breast cancer (MBC) receiving first-line endocrine-based therapy (palbociclib plus letrozole and letrozole alone). Patients and methods: Treatment-naïve postmenopausal women with estrogen receptor-positive (ER+)/human epidermal growth factor receptor 2-negative (HER2−) MBC were randomized 2 : 1 to palbociclib plus letrozole ( n  =   444) or placebo plus letrozole ( n  =   222). Patient-reported outcomes were assessed at baseline, day 1 of cycles 2 and 3, and day 1 of every other cycle from cycle 5 using the Functional Assessment of Cancer Therapy (FACT)-Breast and EuroQOL 5 dimensions (EQ-5D) questionnaires. Results: As of 26 February 2016, the median duration of follow-up was 23 months. Baseline scores were comparable between the two treatment arms. No significant between-arm differences were observed in change from baseline in FACT-Breast Total, FACT-General Total, or EQ-5D scores. Significantly greater improvement in pain scores was observed in the palbociclib plus letrozole arm (−0.256 versus −0.098; P  =   0.0183). In both arms, deterioration of FACT-Breast Total score was significantly delayed in patients without progression versus those with progression and patients with partial or complete response versus those without. No significant difference was observed in FACT-Breast and EQ-5D index scores in patients with and without neutropenia. Conclusions: Overall, women with MBC receiving first-line endocrine therapy have a good QOL. The addition of palbociclib to letrozole maintains health-related QOL and improves pain scores in treatment-naïve postmenopausal patients with ER+/HER2− MBC compared with letrozole alone. Significantly greater delay in deterioration of health-related QOL was observed in patients without progression versus those who progressed and in patients with an objective response versus non-responders. ClinicalTrials.gov: NCT01740427 (https://clinicaltrials.gov/ct2/show/NCT01740427 )